β-D-XYLOSIDASE 4 modulates systemic immune signaling in Arabidopsis thaliana - Bauer, Kornelia; Nayem, Shahran; Lehmann, Martin; Wenig, Marion; Shu, Lin-Jie; Ranf, Stefanie; Geigenberger, Peter; Vlot, A. Corina (Frontiers in Plant Science, 2023)
Pectin- and hemicellulose-associated structures of plant cell walls participate in defense responses against pathogens of different parasitic lifestyles. The resulting immune responses incorporate phytohormone signaling components associated with salicylic acid (SA) and jasmonic acid (JA). SA plays a pivotal role in systemic acquired resistance (SAR), a form of induced resistance that - after a local immune stimulus - confers long-lasting, systemic protection against a broad range of biotrophic invaders. β-D-XYLOSIDASE 4 (BXL4) protein accumulation is enhanced in the apoplast of plants undergoing SAR. Here, two independent Arabidopsis thaliana mutants of BXL4 displayed compromised systemic defenses, while local resistance responses to Pseudomonas syringae remained largely intact. Because both phloem-mediated and airborne systemic signaling were abrogated in the mutants, the data suggest that BXL4 is a central component in SAR signaling mechanisms. Exogenous xylose, a possible product of BXL4 enzymatic activity in plant cell walls, enhanced systemic defenses. However, GC-MS analysis of SAR-activated plants revealed BXL4-associated changes in the accumulation of certain amino acids and soluble sugars, but not xylose. In contrast, the data suggest a possible role of pectin-associated fucose as well as of the polyamine putrescine as regulatory components of SAR. This is the first evidence of a central role of cell wall metabolic changes in systemic immunity. Additionally, the data reveal a so far unrecognized complexity in the regulation of SAR, which might allow the design of (crop) plant protection measures including SAR-associated cell wall components.